1980
DOI: 10.1111/j.1469-8749.1980.tb03714.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sleep Spindle Activity During Infancy

Abstract: SUMMARY Sleep spindle activity was evaluated in 32 twins at 52 weeks postconceptional age. Significantly increased mature spindle activity was seen in infants born at older gestational ages, in females, and in infants who were stressed by intra‐uterine growth retardation or with mild postnatal respiratory illness. RESUME Facteurs de preAdiction de I'activité de sommeil en fuseau au cours de la première enfance L'activité de sommeil en fuseau a été recherchée chez 32 jumeaux a 52 semaines d'age conceptuel. Une … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 14 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…However, their independent occurrence )asynchrony( below 2 years of age is common and a normal finding. [9][10][11][12] These sleep milestones are consistent between subjects, and therefore they are an essential indication of functional maturation. 13 Chatburn et al 14 found that sleep spindle activity was associated with various aspects of maturation and is an integral part of brain development.…”
Section: Discussionmentioning
confidence: 97%
“…However, their independent occurrence )asynchrony( below 2 years of age is common and a normal finding. [9][10][11][12] These sleep milestones are consistent between subjects, and therefore they are an essential indication of functional maturation. 13 Chatburn et al 14 found that sleep spindle activity was associated with various aspects of maturation and is an integral part of brain development.…”
Section: Discussionmentioning
confidence: 97%